Tradisi Mamukek sebagai Ketahanan Pangan Biru Nelayan Artisanal dengan Pendekatan Common Property di Nagari Sungai Pinang, Pesisir Selatan, Sumatera Barat - Muhammad Alif Athallah; Basyarul Aziz; Abbhie Zacky Anggara; Tedy Jhonatan; Gusneli Gusneli; Esa Rahmadhani (Department of Anthropology, 2026)
The mamukek tradition is a collective fishing practice preserved in Nagari Sungai Pinang, Pesisir Selatan Regency, West Sumatra, serving as a vital component of the